Membangun Motivasi Belajar Mahasiswa Melalui Kajian Sejarah Minangkabau - Joni Indra Wandi; Lusi Tania Agustin; M. Hubbal Khair; Ismawati Sitorus; Cipto Duwi Priyono (Journal Education And Islamic Studies, 2023)
This article aims to present how the study of Minangkabau history can be utilized as a tool to enhance student motivation for learning. The research was conducted at the West Sumatra Islamic Institute (IAI Sumbar). A qualitative methodology was employed in this study to assess the extent to which students' understanding of the historical experiences and perceptions relating to the study of history impacts their motivation to learn. Participants in this research were students at IAI Sumatera Barat who were engaged in the study of Minangkabau history. Data were gathered through in-depth interviews and participatory observations. The research findings indicate that the study of Minangkabau history has a positive impact on student motivation to learn. It was observed that a deep understanding of the cultural heritage and the struggles of their ancestors in the historical study has ignited a sense of pride and cultural identity among the students. This, in turn, has sparked their interest in delving deeper into the learning materials and broadening their knowledge of local history and culture. Furthermore, the study of history is also regarded as a source of inspiration in overcoming academic challenges and cultivating perseverance in learning. In conclusion, this research suggests that the use of Minangkabau history studies as a pedagogical approach plays a significant role in building student motivation to learn at IAI Sumatera Barat.